(untitled) (Research, Society and Development, 2023)
Introduction: Aging is a natural process in human beings. However, the physiological changes that occur at these ages can generate changes in the mechanical, physical and biochemical functions of the elderly. Due to this bias, one of the main impasses that affect these individuals today is the dementia syndrome. To analyze the medical records of users diagnosed with dementia and the associated factors in selected Basic Health Units in the city of Itaperuna-RJ. Methodology: The study will be cross-sectional and the medical records of patients registered in selected Health Units in the city of Itaperuna-RJ will be identified and selected for the research. The results obtained will present numerical data about the search. Subsequently, they will be analyzed and compared with bibliographic research on the subject. Soon, a conclusive analysis of the scientific study will be carried out. Result: 9 articles were analyzed on the associated factors in the inclusion and exclusion criteria. Discussion: In recent years, there has been an increasing number of individuals over 60 years of age. Thus, there is a need for greater public health attention to this fact. Since aging entails adjacent diseases, such as chronic diseases that are associated with the dementia syndrome. Therefore, a more detailed study on the subject is necessary. Conclusion: Therefore, it is evident that aging requires in-depth studies and research because it is a public health issue. This is due to the fact that such pathology has an impact on the way of life of individuals.